Development of Genomic Resources and Identification of Genetic Diversity and Genetic Structure of the Domestic Bactrian Camel in China by RAD Sequencing - Liu, Chenmiao; Chen, Huiling; Ren, Zhanjun; Yang, Xuejiao; Zhang, Chengdong (Frontiers in Genetics, 2020)
The domestic Bactrian camel is indispensable to agricultural production in the desertification area of China owning to its endurance to hunger and thirst, cold resistance, drought resistance, and good long-distance transportation. Therefore, it is necessary to investigate the genetic diversity, genetic structure, and genes with important roles in the evolution of this species. In this study, 1,568,087 SNPs were identified in 47 domestic Bactrian camels inhabiting four regions of China, namely Inner Mongolia, Gansu, Qinghai, and Xinjiang, by restriction site associated DNA sequencing (RAD-seq). The SNP data were used for nucleotide diversity analysis (π) and linkage disequilibrium (LD) attenuation analysis to elucidate the genetic diversity of the domestic Bactrian camel in the four regions studied. Results showed that Xinjiang camels had the highest nucleotide diversity and the fastest decay rate of the LD coefficient; therefore, Xinjiang camels had the highest genetic diversity. Structure analysis, principal component analysis (PCA), and phylogenetic tree construction by the neighbor-joining (NJ) method showed that Qinghai camels clustered separately, at a larger phylogenetic distance from camels in the other regions. Through analyses of selection signals, it was found that the number of selected genes shared by Inner Mongolia camels, Qinghai camels, Xinjiang camels, and Gansu camels was 7, 24, 25, and 113, respectively. The shared selected genes of the domestic Bactrian camel in the four regions were further analyzed, and three shared genes (GRIA3, XIAP, and THOC2) of the domestic Bactrian camel in China were identified. Gene Ontology (GO) classification and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis were performed on the shared selected genes of the domestic Bactrian camel in all four regions studied. Across all regions, genes involved in the cellular process were the most abundant subcategory under biological process. Cell and cell part represented the main proportion of genes under cellular component. Binding represented the main molecular function. In addition, the shared selected genes of the domestic Bactrian camel in the four regions of China were significantly enriched in the long-term depression pathway. The research should enable further study of the genetic resources of the domestic Bactrian camel.